(untitled) - Otani, Ryokichi (Tokyo, 1932)
A fascianting account of the life and methods of Ino (1745 - 1818), pioneer surveyor of Japan. A successful brewer, he learned his art after age fifty. The accuracy of his maps of the Japanese coasts astonished Europeans and rendered detailed mapping by the British Navy unnecessary. Ito is a much prized cult figure of Japanese engineers even in these days.
Keywords: Cartography,Vẽ bản đồ; History,Lịch sử; Japan,Nhật Bản